Tele-Evaluation based on quality and quantity of hemiplegic children movements - M. Elsaeh, M. Djemai, M. Bouri (Journal of Pure & Applied Sciences, 2020)
Continuation of rehabilitation processes is a key element for success. Home-based therapy has become one of the major therapies’ types in terms of continuation. Evaluate patients’ progress in home-therapy is critical for therapeutics. This study concerns meanly on simulating human techniques of evaluation by recruiting available mathematics methods in order to make assessment decisions. A haptic device is embedded with virtual reality scenarios in order to build the upper limbs tele-rehabilitation system. Fuzzy logic concept is used in this novel evaluation method to enable us to ensemble both: I) Data related to the quality of movements; and II) Data related to the quantity of those movements. Then, calculate the functional enhancement of concerned affected upper limbs by study the changes of the function motions of those limbs. Finally, provide therapists with objective evaluation to help them judging the rehab process. The evaluation system was used for two children who were used the rehab system.